1979
DOI: 10.1111/j.1365-2141.1979.tb05865.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course in 28 Unselected Patients with Aplastic Anaemia Treated with Anabolic Steroids

Abstract: Twenty-eight unselected patients with histologically proven aplastic anaemia were electively treated with anabolic steroids (75-150 mg orally q.d.) Additional supportive treatment with blood cell components and antibiotics was given if indicated. Response to therapy was defined as favourable if after 3 months of anabolic therapy overt bleeding tendency had disappeared, there was no need for transfusion therapy, a spontaneous increase of haemoglobin had occurred of greater than 3 g/dl above the initial level, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Furthermore, PI(Naj) and PI(Lyn) appeared rather robust to application to patients fulfilling more extensive criteria of selection, while our EP on the other hand seemed to retain its discriminative capacity in the more restricted groups of patients with A A retrospectively or initially. Thus, our study supports the predictive value of PI(Lyn) and DS(Cam) which has been questioned by te Velde & Haak (20) and van Hengstum et a1 (24), respectively. Conversely, EP(Roz) was not found significantly predictive, but PI(Lyn) also appeared less discriminative than originally reported (2).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, PI(Naj) and PI(Lyn) appeared rather robust to application to patients fulfilling more extensive criteria of selection, while our EP on the other hand seemed to retain its discriminative capacity in the more restricted groups of patients with A A retrospectively or initially. Thus, our study supports the predictive value of PI(Lyn) and DS(Cam) which has been questioned by te Velde & Haak (20) and van Hengstum et a1 (24), respectively. Conversely, EP(Roz) was not found significantly predictive, but PI(Lyn) also appeared less discriminative than originally reported (2).…”
Section: Discussionsupporting
confidence: 89%
“…One group of hormones with known effects on in vitro erythropoiesis, the steroids, has been used extensively in the treatment of various anemia states, including aplastic anemia, myelofibrosis, refractory anemia, chronic lymphocytic leukemia, and the anemias of chronic renal failure and inflammatory disease [13,14]. Reports of steroid dependency in some patients with bone marrow failure states are well known [15][16][17], whereas other studies have demonstrated that the vast majority of patients treated with these agents show no hématologie improvement following therapy [18][19][20][21]. Clearly, an in vitro method to predict clinical response to steroids would be of great value in the selection of patients for this form of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of androgen treatment on erythropoiesis have been well established (McCullagh and Jones 1942) and have been used in the treatment of a variety of anaemias (Hendler et al 1974;Hengstum et al 1979;Najean 1981). This results from a direct effect on the bone marrow (Mirand and Murphy 1971;) and from enhancement of erythropoietin production, even in anephric patients (Naets and Wittek 1968;Shahidi 1973).…”
Section: Haematopoietic Systemmentioning
confidence: 99%